Associations among fear of childbirth, resilience and psychological distress in pregnant women: A response surface analysis and moderated mediation model - Mei, Xiaoxiao; Mei, Ranran; Liu, Yuling; Wang, Xinqin; Chen, Qianwen; Lei, Youjin; Ye, Zengjie (Frontiers in Psychiatry, 2022)
Introduction Prenatal psychological distress is prevalent during pregnancy. This study aimed to estimate the associations among fear of childbirth, resilience and psychological distress. Methods A total of 1,060 Chinese pregnant women were enrolled from Be Resilient to Postpartum Depression (ChiCTR2100048465) and the following instruments were administered to them: Childbirth Attitudes Questionnaire, Connor-Davidson Resilience Scale, Perceived Social Support Scale, General Self-Efficacy Scale, Adverse Childhood Experience scale and Hospital Anxiety and Depression Scale. A dominance, a response surface analysis and a moderated mediation analysis were performed. Results In terms of psychological distress, resilience and fear of childbirth could explain 41.6% (0.148/0.356) and 33.1% (0.118/0.356), respectively. Pregnant women with high resilience-low fear of childbirth had significantly lower levels of psychological distress than those with low resilience-high fear of childbirth. The indirect effects of fear of childbirth on psychological distress through resilience was significantly (B = 0.054, 95% CI 0.038 to 0.070). The interactions between fear of childbirth and adverse childhood experiences (β = 0.114, 95% CI −0.002 to 0.231, p = 0.054) and between resilience and adverse childhood experiences (β = −0.118, 95% CI −0.222 to −0.012, p < 0.05) were significant. Conclusion Resilience, fear of childbirth and adverse childhood experiences may be three important factors to psychological distress in Chinese pregnant women.